2021
DOI: 10.1002/phar.2506
|View full text |Cite
|
Sign up to set email alerts
|

The impact of statin use prior to intensive care unit admission on critically ill patients with sepsis

Abstract: Objective: To evaluate the impact of pre-intensive care unit admission (pre-ICU) statin use on all-cause in-hospital mortality and ICU length of stay (LOS). Design: Retrospective cohort study. Setting: Adult ICUs at tertiary hospitals. Patients: Adult critically ill patients diagnosed with sepsis admitted to the ICUs. Intervention: The exposure was pre-ICU statin prescription (statin users); unexposed represented absence of pre-ICU prescription (non-users). Measurement and Main Results: We used the 2001-2012 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The association of pre-ICU statin use with mortality showed no sex differences but differed with AKI stages. Finally, sensitivity analyses con rmed the robustness of our results.Chinaeke et al showed that patients in ICU with sepsis who had pre-ICU statin use had decreased mortality and ICU LOS, demonstrating the pleiotropic effect of statin[21]. Our study was based on ICU patients with AKI, similar but different population with Chinaeke's, also showed an association between pre-ICU statin use and outcomes.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…The association of pre-ICU statin use with mortality showed no sex differences but differed with AKI stages. Finally, sensitivity analyses con rmed the robustness of our results.Chinaeke et al showed that patients in ICU with sepsis who had pre-ICU statin use had decreased mortality and ICU LOS, demonstrating the pleiotropic effect of statin[21]. Our study was based on ICU patients with AKI, similar but different population with Chinaeke's, also showed an association between pre-ICU statin use and outcomes.…”
supporting
confidence: 55%
“…We de ned pre-ICU statin users as patients with records of statins, including the brand and generic names of medicines, otherwise as non-users. The type of statin was referred to other authors' study based on MIMIC-III database [21], it is also applicable to MIMIC-IV database through careful veri cation. The prescriptions of the medicines were recorded in the MIMIC-IV v1.0 "PRESCRIPTION" le.…”
Section: Medication Exposurementioning
confidence: 99%
“…Finally, sensitivity analyses confirmed the robustness of our results. Chinaeke et al showed that patients in ICU with sepsis who had pre-ICU statin use had decreased mortality and ICU LOS, demonstrating the pleiotropic effect of statin (20). This study was based on ICU patients with AKI, similar but different population from theirs, and showed an association between pre-ICU statin use and outcomes.…”
Section: Discussionmentioning
confidence: 68%
“…The schematic that illustrates statin exposure and follow-up was shown in Supplementary Figure S1. The types of statin used were referred to other study based on the MIMIC-III database (20) and they are also applicable to the MIMIC-IV database through our careful verification. The prescriptions of the medicines were recorded in the MIMIC-IV (version 1.0) "Prescription" table.…”
Section: Medication Exposurementioning
confidence: 99%
“…If there is no convincing evidence that statins as a treatment initiated for sepsis improves survival, the effect of chronic statin use on the incidence and outcome of sepsis is less clear, as most randomized control trials excluded patients previously on statins [ 31 , 32 ]. Several studies have suggested that chronic statin use may be associated with decreased rate of severe sepsis, ICU admission [ 35 ] and mortality [ 36 , 37 ]. A large Canadian population-based cohort analysis including approximately 141,000 patients reported that the use of statins in patients with atherosclerosis was associated with a reduced risk of subsequent sepsis (HR 0.81, 95% CI 0.72–0.90), severe sepsis (HR 0.83, 95% CI 0.70–0.97) and fatal sepsis (0.75, 95% CI 0.61–0.93) after adjustment for demographic characteristics, comorbidities and sepsis risk factors [ 14 ].…”
Section: Discussionmentioning
confidence: 99%